A Machine Learning Classification Application to Identify Inefficient Novice Programmers - Khan I.; Al-Mamari A.; Al-Abdulsalam B.; Al-Abdulsalam F.; Al-Khansuri M.; Iqbal Malik S.; Ahmad A.R. (Springer Science and Business Media Deutschland GmbH, 2023)
Data mining; Graphical user interfaces; Learning algorithms; Machine learning; Nearest neighbor search; Academic performance; Application layers; Computer science students; Educational data mining; Educational Institutes; K-near neighbor; Machine learning classification; Nearest-neighbour; Novice programmer; Productive tools; Students